2018
DOI: 10.1039/c7ra12352c
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the efficiency of single junction kesterite solar cell using Ag mixed Cu2ZnSnS4 active layer

Abstract: A CdS/ACZTS/CZTS single junction kesterite solar cell with 17.59% efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…The same electric field profile has also been reported in Ref. [20] where the peaks at the interfaces is noticeable and supports an improved V oc . The electric field distribution has also been shown in 3D (Fig.…”
Section: Electrical Simulationsupporting
confidence: 88%
See 2 more Smart Citations
“…The same electric field profile has also been reported in Ref. [20] where the peaks at the interfaces is noticeable and supports an improved V oc . The electric field distribution has also been shown in 3D (Fig.…”
Section: Electrical Simulationsupporting
confidence: 88%
“…3d in Ref. [20]. Saha et al have also reported that G tot has a high peak at the CZTSe side of the interface since CZTSSe has a higher absorption compared to CdS [20].…”
Section: Optical Simulationmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to the possible n‐type and large band‐offset with CdS, ACZTS(Se) has been investigated as n‐type layer in CZTS/AZTS heterojunctions leading to an encouraging 4.5% efficiency, with even a p‐type AZTS/n‐type AZTS homojunction being later considered, though with a more limited 0.9% efficiency reported so far . These preliminary approaches are not without future, as a recently published theoretical work proposed a CdS/ACZTS/CZTS (n/p/p+) solar cell with a potential efficiency close to 20%, but no experimental demonstration was made up to date. Nevertheless, the latest progress using solution‐processed (Cu 1‐ x Ag x ) 2 ZnSn(S,Se) 4 with 3% of Ag (with respect to Cu) has reported a 10.4% efficiency, and 10.2% using co‐evaporation for the pure selenide compound with up to 10% of Ag, hence revitalizing the interest in the Ag‐based kesterite alloys and paving the way toward future improvements.…”
Section: Challenges and Perspectives: How To Improve The Kesterite Efmentioning
confidence: 99%
“…10 (c) and (d) indicates that with increasing the concentration of Ag doping, the band tailing is significantly reduced. The improvement of EQE can be attributed to the optimization of band alignment between CZTSe and CdS heterojunction [15,19,47] . Many reports confirmed that with appropriate Ag doping, the concentration of Cu Zn defects can be significantly reduced [2] .…”
Section: The Performance Of Front Ag-gradient Acztse Thin Film Solar Cellsmentioning
confidence: 99%